2015
DOI: 10.1155/2015/145918
|View full text |Cite
|
Sign up to set email alerts
|

Shrinkage Behaviour of Fibre Reinforced Concrete with Recycled Tyre Polymer Fibres

Abstract: Different types of fibres are often used in concrete to prevent microcracking due to shrinkage, and polypropylene fibres are among the most often used ones. If not prevented, microcracks can lead to the development of larger cracks as drying shrinkage occurs, enabling penetration of aggressive substances from the environment and reducing durability of concrete structures. The hypothesis of the present research is that polypropylene fibres, used in concrete for controlling formation of microcracks due to shrink… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
32
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 12 publications
6
32
0
2
Order By: Relevance
“…The influence of RTPFc fibers on autogenous deformations can be explained by the fact that the modulus of elasticity of fibers is higher compared to the modulus of concrete during first 24 hours of hardening, which is why the presence of those fibers has positive influence on stress distribution and lower shrinkage stains. The obtained results are in accordance with the literature data for concrete with PP fibers [4,5,25,26] but also with results obtained with ordinary and sprayed concrete with RTPF fibers [11,27,28].…”
Section: Compressive Strengthsupporting
confidence: 91%
“…The influence of RTPFc fibers on autogenous deformations can be explained by the fact that the modulus of elasticity of fibers is higher compared to the modulus of concrete during first 24 hours of hardening, which is why the presence of those fibers has positive influence on stress distribution and lower shrinkage stains. The obtained results are in accordance with the literature data for concrete with PP fibers [4,5,25,26] but also with results obtained with ordinary and sprayed concrete with RTPF fibers [11,27,28].…”
Section: Compressive Strengthsupporting
confidence: 91%
“…In particular, recycled tyre polymer fibre (RTPF) extracted from end-oflife tyres through thermomechanical processes is regarded as a promising recycled material [33], which can be incorporated into concrete for the sake of improving FRC's sustainability and mitigating the environmental impact caused by landfilling the waste tyres (approximately 500 million landfilled waste tyres every year [34]). Recently, a few studies [35][36][37][38][39][40][41] have been carried out to estimate the effect of RTPF on mechanical properties (static and dynamic) and durability performance of normal concrete. Baričević et al [35,36] concluded that the incorporation of RTPF can reduce the early-age shrinkage deformation of concrete and enhance its resistance to freeze-thaw cycles.…”
Section: Introductionmentioning
confidence: 99%
“…Serder et al (2015) [10], studied polypropylene fibre and recycled tyre polymer fibre in NAC. M-50 mix design was made and it was found that slump decreases with the addition of fibres but addition of 1% RTPF fibres by weight of aggregates did not affect negatively the workability.…”
Section: Workabilitymentioning
confidence: 99%